TANTANGAN KEBERLANJUTAN PEKEBUN KELAPA SAWIT RAKYAT DI KABUPATEN PELALAWAN, RIAU DALAM PERUBAHAN PERDAGANGAN GLOBAL - Sakti Hutabarat (Masyarakat Indonesia, 2017)
Oil palm smallholders are potential actors to be included in the global palm oil market. Smallholder plantations account for 41.4% of total oil palm plantation areas and represents 36.6% of total CPO produced in Indonesia in 2015. The number of farmers involves in oil palm plantation encompass 2.3 million farmers which have been  an important driver for economic growth in rural areas. However, oil palm smallholders are vulnerable from issues related to unsustainable production including environmental, social and legal issues which might lower access and exclude smallholder access to global market. The objective of this study is to analyze position and capacity of oil palm smallholders in facing global change in international market. Population of this study is oil palm smallholder farmers in Ukui Subdistrict, Pelalawan District, Riau Province which consist of RSPO-certified independent smallholders, Non-certified independent smallholders, and RSPO-certified scheme smallholders. The sample size were 220 farmers and chosen randomly from each group (80, 60 and 80 farmers for each group respectively). The study found that majority of the farmers still apply traditional practices in their plantations and far below the standard of good agricultural practices and certification standards. The challenges faced by the Amanah Association to obtain RSPO certificate is not easy to follow by other smallholders. Therefore, external supports from government and private actors are needed to improve farmers’ capacity to meet and comply with certification and to include small-scale farmers in the palm oil global supply chain.Keywords: Independent smallholders, scheme smallholders, oil palm, certification, global market ABSTRAKPekebun kelapa sawit merupakan aktor yang berpotensi menjadi bagian penting dari perdagangan minyak sawit global. Luas perkebunan kelapa sawit rakyat mencapai 41,4% dari seluruh area perkebunan sawit Indonesia dengan produksi 36,6% dari total produksi minyak sawit Indonesia pada 2015. Jumlah pekebun kelapa sawit rakyat mencapai 2,3 juta; ini merupakan jumlah yang cukup signifikan sebagai penggerak perekonomian di pedesaan. Namun, pekebun kelapa sawit rakyat sangat rentan terhadap berbagai isu (lingkungan, sosial, dan legalitas) yang dapat menghambat akses pasar di rantai suplai internasional. Studi ini bertujuan menganalisis posisi dan kapasitas pekebun kelapa sawit rakyat dalam menghadapi perubahan global perdagangan internasional. Populasi penelitian ini adalah pekebun kelapa sawit rakyat di Kecamatan Ukui, Kabupaten Pelalawan, Provinsi Riau, yaitu pekebun kelapa sawit swadaya bersertifikat RSPO, pekebun kelapa sawit swadaya non-RSPO, dan pekebun kelapa sawit plasma bersertifikat RSPO. Jumlah sampel ditentukan sebesar 220 pekebun dan dipilih secara acak untuk setiap grup (80, 80, dan 80 pekebun). Studi ini memperlihatkan sebagian besar pekebun masih menjalankan bisnis kelapa sawit secara tradisional. Praktik pertanian yang dilakukan masih jauh dari praktik pertanian yang terbaik (good agricultural practices) ataupun dari standar sertifikasi yang ada. Perjuangan pekebun kelapa sawit swadaya Amanah di Kecamatan Ukui untuk memperoleh sertifikasi RSPO memperlihatkan bahwa tantangan tak mudah dicapai pekebun swadaya lain. Campur tangan pemerintah dan aktor lain sangat dibutuhkan pekebun kelapa sawit swadaya untuk dapat disertifikasi dan menjadi bagian dari rantai suplai kelapa sawit internasional.Kata kunci: Pekebun kelapa sawit rakyat, pekebun swadaya, pekebun plasma, kelapa sawit, sertifikasi, perdaganganglobal